Comparison of active release and post-isometric relaxation techniques on functional performance in patients with chronic lateral epicondylitis - Hanif, Ans; Hafeez, Sana; Arif, Tooba; Habib, Sidra (Journal of Musculoskeletal Surgery and Research)
Objectives: Lateral epicondylitis (LE) occurs as a result of repetitive strain near the place of origin of the extensor carpi radialis brevis tendon. This is due to eccentric overload and repetition, causing chronic degeneration of the forearm’s common extensor tendons, which are attached to the lateral epicondyle of the humerus. This study aimed to assess the comparative effects of post-isometric relaxation (PIR) and active release techniques (ARTs) on pain inhibition, grip strength, and functional ability among individuals suffering from chronic LE. Methods: A randomized clinical trial was conducted on 30 individuals suffering from chronic LE. All of the subjects were randomly assigned to one of two treatment groups: PIR method or active release approach. Both groups received 12 sessions over four weeks. The numerical pain rating scale (NPRS), handheld dynamometer, and patient-rated tennis elbow evaluation (PRTEE) were used to assess the impacts of therapy before and after treatment sessions. Results: The results showed that the NPRS pain score, strength of the grip, and functional performance all showed substantial differences between the two groups (P < 0.05) as well as within-group differences (P < 0.05). Conclusion: The study concluded that PIR techniques were more effective as compared to ARTs for pain reduction, improved strength of gripping, enhanced functionality, and showed better outcomes in terms of mean difference of NPRS, dynamometer, and PRTEE scoring across the groups.